Differentially expressed proteins obtained by label‐free quantitative proteomic analysis reveal affected biological processes and functions in Western diet‐induced steatohepatitis. Issue 6 (17th March 2021) - Moreto, Fernando; Ferron, Artur J. T.; Francisqueti‐Ferron, Fabiane V.; D'Amato, Alfonsina; Garcia, Jessica L.; Costa, Mariane R.; Silva, Carol Cristina V. A.; Altomare, Alessandra; Correa, Camila Renata; Aldini, Giancarlo; Ferreira, Ana Lucia A.
Abstract: Nonalcoholic steatohepatitis (NASH) is a pathological manifestation with a progressive incidence in response to the epidemic of hepatic steatosis caused primarily by excessive energy intake. The present study unravels affected biological processes and functions by the presence of NASH in rats using a label‐free quantitative proteomic strategy. NASH was induced by a Western high‐sugar and high‐fat diet for 20 weeks. The liver tissue was collected for histology and for a mass spectrometry‐based proteomic protocol. The NASH group showed severe lipidosis, hepatocyte ballooning, and the presence of collagen deposition. Among upregulated proteins in NASH perilipin‐2 (Plin‐2; F6QBA3; difference [diff]: 2.29), ferritin heavy (Fth1; Q66HI5; diff: 2.19) and light (Ftl1; P02793; diff: 1.75) chains, macrophage migration inhibitory factor 1 (Mif; P30904; diff: 1.69), and fibronectin (Fn1; F1LST1; diff: 0.35) were observed, whereas among downregulated proteins,  plectin (Q6S399; diff: −3.34), some Cyp2 family proteins of the cytochrome P450 complex, glutathione S‐transferases, flavin‐containing monooxygenase 1 (Fmo1; P36365; diff: −2.08), acetyl‐CoA acetyltransferase 2 (Acat2; Q5XI22; diff: −2.25), acyl‐CoA oxidase 2 (Acox2; F1LNW3; diff: −1.59), and acyl‐CoA oxidase 3 (Acox3; F1M9A7; diff: −2.41) were observed. Also, biological processes and functions such as LPS/IL‐1 inhibition of RXR, fatty acid metabolism, Nrf2‐mediated oxidative stress response, xenobiotic metabolism, and PXR/RXR and CAR/RXR activations were predicted to be affected. In conclusion, the liver of rats with NASH induced by Western diet shows a decreased capacity of metabolizing lipids, fatty acids, and xenobiotic compounds that predispose fibrosis development. Abstract : Biological processes and functions affected in liver in the time‐course development of western diet induced NAFLD and NASH with early‐stage fibrosis.